117 - OPINION OF NURSING AUXILIARIES ABOUT MUNICIPAL LAW ON RIGHTS OF USERS IN HEALTH CARE IN THE CITY OF NATAL / RN. (Fiep Bulletin - online, 2011)
This is a descriptive study aimed to evaluate the opinion of nursing auxiliaries on Patients' Rights in the city of Natal / RN. It was carried out in January 2001. It´s considered a pre-test to develop a project, posteriorly. Participants were fifteen in a random sample of nursing auxiliaries of a public hospital, in accordance with the legal precepts of Resolution No. 196/CNS/1996. Findings shows that 90% were unaware of the existence of laws that ensured the patients' rights, 90% of respondents believe that managers and leaders of the institution in which they work do not know, except in cases of legal representation; 80% of the auxiliary nursing respondents believe that most users of health services ignore them. It is suggested a critical reflective rethink on ethics in nursing approach, both in professional practice through continuing education, or in the learning process from a pivot point coordinated with other content.
Keywords: Nursing; Patients Right; nursing auxiliaries